Aspekty duchowe chronotopu w powieściach emigracyjnych Iwana Szmielowa - Andruszko, Czesław; Horczak, Dorota (Wydział Neofilologii UAM w Poznaniu, 2019)
The work includes a detailed analysis of chronotope category in Ivan Shmelyov’s emmigrant novels. There were examinated different pieces of writings with respect to form and plot, such as The Sun of the Dead (Солнце мёртвых, 1923), The Nanny from Moscow (Няня из Москвы, 1932–1933), Bogomolye (Богомолье, 1930–1931), Year of the Lord (Лето Господне, part 1.: 1927–1931, part 2. and 3.: 1934–1944), The heavenly ways (Пути господне, vol. 1.: 1935–1936, vol. 2.: 1944−1947). The work consists of five chapters and each of which is devoted to mentioned novels of Shmelyov. It also contains an introduction and a bibliography. The first chapter is titled The Formation of Spiritual Chronotope In Early Writings of Shmelyov. It gives the whole range of examples pointing out a great influence of Lev Tolstoy on Shmelyov. Ivan Shmelyov was interested in the author of War and Peace as in a human being and an artist who had created the place to a characteristic author’s pantheism. The second chapter, titled The Apocaliptic Time and the Space In Epos “The Sun of the Dead”, shows the beginning of the author’s career in emmigration in the light of a revolutionary epos, that brought to Shmelyov world-wide fame. Ivan Shmelyov used some elements of skaz and ornamental prose to create an apocalyptic picture of time. This chapter contains the author’s polemics with Boris Pilniak’s history conception. In the third chapter, The Chronotope of Exodus In The Novel ”The Nanny from Moscow”, the author turned to the historical past of Russia in order to notice the whole range of analogies with the biblical period of humankind, that had survived thanks to amazing power of the Orthodox Church. The fourth chapter, titled The Panetheism-Sacral Paradigm of Time and a Space in Work “Bogomolye” gives a comparative analysis as far as both novels had been written in a form of dilogy. They share the author’s unity of an idea. It’s essence is reflected in the beauty of human beings created by the God. The fifth chapter, The Paschal Atributes of Chronotope In the Story "The heavenly ways", shows new perspectives to examine the unfinished piece of writing. The story strongly reflects the spiritual evolution of Shmelyov, who repeated after Leibniz that human being lived on the world best ever.
Духовные аспекты хронотопа эмиграционных романов Ивана Шмелева
Keywords: Iwan Szmielow; powieść emigracyjna; aspekty duchowe chronotopu; Ivan Shmelyov